Religious Dynamics in Border Regions in the Context of Interfaith and External Relations (Based on Materials from the Republic of Karelia, 1940–1980s) - Ljudmila I. Vavulinskaya; Svetlana E. Yalovitsyna (Финно-угорский мир)
Introduction. The religious policy of the Soviet atheist state underwent several transformations between the 1940s and the 1980s. The religious “thaw” of the early post-war years was replaced by renewed pressure on the Church in the late 1950s. In Karelia, these processes had distinct characteristics shaped by its borderland position, proximity to Finland, and the presence of Finnish Lutherans within the republic’s population. At the same time, Karelia was traditionally regarded as a region with a predominance of Orthodox believers, which led researchers to focus primarily on the Orthodox history of the area. This article aims to examine the impact of Karelia’s borderland status on the region’s religious landscape.